PENGELOMPOKAN ANGGOTA DIVISI HIMPUNAN MAHASISWA JURUSAN PADA UNIVERSITAS “XYZ” DENGAN METODE K-MEANS CLUSTERING - Maydina Anggita Pravita Sari; Umi Chotijah (Universitas Islam Balitar, 2022)
The Department of Student Association is a human group formed to have the same goal in building an organization in higher education. So far, HMJ has carried out the process of grouping daily management into each division manually and there is no objective process that causes several candidates for daily management to be placed not according to their abilities. To solve the existing problems, a study was conducted using the K-means Clustering method. The K-Means method is very much needed because it can determine the grouping of candidates for the daily committee using variables that can be a guide for making decisions for candidates who will be selected as daily administrators of the student association majors. In the K-Means calculation, the results of the grouping of candidates for the daily management of the student association majors in each division are obtained according to the criteria determined by the HMJ. Based on the results of the comparison calculations with the original data from the HMJ interview and the results of calculations using K-Means, an accuracy value of 25% was calculated using the accuracy formula in the results and discussion chapter. Therefore, in the further research, weights can be added to the criteria and the data is reproduced so that the accuracy values can be compared in research using the K-Means method.